Technique for Overcoming Trauma in Adolescents - Haryanti, Aprilia (Journal of Educational Studies, 2024)
Trauma is an experience that can impact a person's mental and emotional health, especially in adolescents who are going through vulnerable stages of development. Trauma is an unpleasant experience in the form of frightening, dangerous, and life-threatening events if the trauma experienced by a person is in the acute and severe stage. Even trauma problems experienced since adolescence can have an impact until adulthood. The cause of trauma can come from violence experienced by someone. Posttraumatic growth is an individual's ability to transform traumatic experiences into positive experiences in his or her life. This article discusses strategies and approaches that can help teens cope with trauma. We'll discuss the definition of trauma, how it impacts teens, and some methods that have been proven successful in helping teens recover from trauma. In addition, a bibliography covering relevant scientific sources will be presented.